" COMPARATIVE CLASSIFICATION OF METHODS OF IN VIVO AND IN VITRO TESTING OF DUST ALLERGENS IN PATIYENTS WITH POLLINOSIS - Irsaliyeva F. X.; Nurmatova N.F; Saidvaliyeva N. B.; Asalov G’. S (Galaxy International Interdisciplinary Research Journal, 2023)
Pollinosis disease is considered one of the most urgent problems of modern medicine. Because this disease is accompaniyed by the development of seasonal allergic rhinitis, conjunctivitis, sometimes bronchial asthma and other symptoms. In the last 15 20 years, the number of allergic diseases on earth is increasing. Pollinosis is the leading share of allergic diseases in Uzbekistan, which means 200 times more than 30 times mor e than tumor disease than 200 times more than rheumatism. 60 patiyents with pollinosis were taken, the results were compared by in vivo and in vitro methods.